Analysing the playground: sensitizing concepts to inform systems that promote playful interaction - Rennick-Egglestone, Stefan; Walker, Brendan; Marshall, Joe; Benford, Steve; McAuley, Derek (Springer, 2011)
Playful interaction in an important topic in HCI research, and there is an ongoing debate about the fundamental principles that underpin playful systems. This paper makes a contribution to this debate by outlining a set of sensitizing concepts which have emerged from an analysis of interaction in the playground; these help explain its appeal to children, and have been selected for their potential to inspire the design of future playful systems. These concepts have emerged from the analysis of material collected during a structured workshop which was organized by the authors, and which was attended by a group of experts. They have also been applied to the design of Breathless, a playful interactive system which has recently been deployed by the authors, and which represents an unusual evolution of the playground swing. The paper concludes with a number of reflections inspired by Breathless. These have been structured through the use of the concepts as an analytical tool.